PERANCANGAN STEGANOGRAFI HIDDEN MESSAGE DENGAN METODE LEAST SIGNIFICANT BIT INSERTION (LSB) BERBASIS MATLAB - Nizirwan Anwar (Jurnal Algoritma, Logika dan Komputasi, 2018)
Steganography (steganography) is the science or technique of art to hide secret messages in other messages so that the existence of such secret messages can not be accessed by others who have no authority. In terms of data security (, text or audio) should follow the appropriate 5 (five) main rules is the factor of confidentiality, integrity, availability, authenticity, and non-repudiation. LSB algorithm method is a method used steganography where the process of combining messages containing text stored in a particular in this format made this research JPG and BMP with a certain pixel size. This research resulted after the process of testing and analyzing using matrix based application (M-File, Matlab) there is no significant change in quality (cover and stego) and text.Keywords:  Steganography, Cover-Image, Stego-Image, LSB Method